2017
DOI: 10.1007/s10567-017-0245-2
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of ADHD Among Diagnosed Children and Their Parents: A Systematic Review Using the Common-Sense Model of Illness Representations

Abstract: Research on children and parents' experiences of ADHD has grown in recent years, attracting attention to their subjective perception of ADHD as a disorder. Theoretical accounts of illness perception suggest that it is multi-dimensional, consisting of at least five core constructs (see the common-sense model of illness representations or CSM: Leventhal et al., in: Rachman (ed) Medical psychology, Pergamon, New York, vol 2, pp 7-30, 1980, in: Baum, Taylor, Singer (eds) Handbook of psychology and health: social p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 209 publications
2
38
0
Order By: Relevance
“…The results have showed that children construct beliefs about the identity of their ADHD, the consequences it has for their life, how long it will carry out and about their ability to control it (if such control is needed). Similar to the results of Wong and colleagues (Wong et al, 2018), it was found that there is a broad variation in those beliefs. This variation makes the CSM particularly useful as a theory as it aims to explain and predict variations between individuals who have similar conditions (Petrie et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results have showed that children construct beliefs about the identity of their ADHD, the consequences it has for their life, how long it will carry out and about their ability to control it (if such control is needed). Similar to the results of Wong and colleagues (Wong et al, 2018), it was found that there is a broad variation in those beliefs. This variation makes the CSM particularly useful as a theory as it aims to explain and predict variations between individuals who have similar conditions (Petrie et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…Wong and colleagues (Wong, Hawes, Clarke, Kohn, & Dar-Nimrod, 2018) have suggested that the model may help us to understand psychosocial outcomes of ADHD in children. In a systematic review of qualitative and quantitative studies on children's perceptions of their ADHD, the researchers categorized the results of those studies according to the CSM dimensions in order to explore characteristics and possible implications of those perceptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms related to ADHD may affect individuals throughout their lifespan, due to complex genetic and neurobiological factors that hamper self-regulation (Tarver, Daley, & Sayal, 2014). A recent review on perceptions of symptoms related to ADHD calls for research that examines the potential implications of children's recognition of their symptoms for their psychological well-being (Wong et al, 2018). The present study represents a response to this request by exploring perceived identity, friendship and well-being in a group of students in which some had an ADHD diagnosis and others did not.…”
Section: Introductionmentioning
confidence: 99%
“…It is mobilized to absolve cultural blame of what may be seen as poor parenting, since asserting that a child "suffers" from a neurobiological disorder is not as delicate a matter as asserting that the child manifests unwanted ADHD-like symptoms in response to an unsteady home life (e.g., Frigerio and Montali 2016;Wong et al 2018). Thus, for parents, an ADHD diagnosis functions as a means to normalize their child and themselves, establish their moral status as competent educators and receive emotional reprieve from guilt (Frigerio and Montali 2016;Schubert et al 2009;Singh 2011;Wong et al 2018). However, receiving an ADHD diagnosis does not necessarily remove the risk of experiencing stigma.…”
Section: Introductionmentioning
confidence: 99%